(untitled) (Educational Dimension, 2020)
The article is devoted to the first Ukrainian research of the audio-verbal memory as the basic modality of the mnemonic processes necessary for successful mastering in text reading skills. More specifically, we observe the correlation between the number of immature mental processes and barriers in the perception and active processing (decoding) of information for elementary school children. We could see that mastering in the reading skills is greatly influenced by impairment of the audio-verbal memory for children with specific disorders of psychological development. This research is the only one in Ukraine that defines and determines the performance indicators of audio-verbal memory, its qualitative and quantitative characteristics for the young children with Dyslexia. Studying the age-related dynamics of memory of children with Dyslexia has shown that its varieties have a different rate of development intensity: the basic parameters of audio-verbal memory of children with impaired reading skills have improved significantly with aging.